The Effect of Simulation Technique on Enhancing Vocational High School Students' Speaking Skill - Yanti, Risky Apriliana (RETAIN, 2021)
This research aims to discover the effect of Simulation Technique on enhancing Vocational High School students’ speaking skill. This study was conducted at one of Vocational High School in Surabaya. It involved 60 students majoring in Office Administration program. The research design used by the researcher was Quasi Experimental. There were two classes that had been investigated, Experimental and Control Group. Each group consisted of 30 students in total. Experimental Group was taught using Simulation Technique, while Control Group was taught using the conventional method. The researcher analyzed the data using T-Test and presented it in the form of Quantitative data (number). According to the result of this study, Simulation Technique is effective to help enhance Vocational High School students’ speaking skill. The effect size of Simulation Technique was calculated using Cohen’s d and it was classified as large effect. In conclusion, the students who were taught using Simulation Technique achieve the better score rather than those who were not.